On large deviations of sums of random variables in the cases of stable limiting distribution - Vaitkus, P. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Вайткус. О больших уклонениях сумм случайных величин в случае предельного устойчивого закона P. Vaitkus. Apie atsitiktinių dydžių sumų didelius nukrypimus stabilaus ribinio dėsnio atveju